Risk management as an objective of management control (Discourse of Law and Administration, 2024)
As of 2010 r. the existing term “financial control” was replaced by the term “management control”, which required the extension of the material scope of control performed in finance public sector units. Risk management serves to increase the likelihood of achieving the individual’s goals through: identification of aims and monitoring of its performance, identification of risk, risk response, remedial actions. The effective use of management control requires correlating it with risk management as well as targeting the achievement of the intended goals, preventing potential irregularities, detecting and correcting errors. Risk management is not processed as assumed, since managers of public sector units were not appropriately trained for this task.
Keywords: financial control; management; risk; standards; guidelines